(3JMaI GdeTJGb efXheI aj Yed GdJQjGbs - (3eMeO Hf bGSe GdMQjQjs
(3ChdgG (B:s
(3GdMeO ddg GdHOjY GdMce hHYO aGdMb GdPi dGjOaY Cf jMQU GdEfSGf ajeG jfaY dGSjeG eG cGf ef OaY GdVQQ hLdH eG jfaY ai MaX GdHTQ s
(3BNQgG (B:s
(3abO TQMJ UhQI GdJQcjH djSJQjM NGWQ GddHjH hGdMeO ddg Ydi eG jSQG MeOkG cKjQkG NGdUkG HdG eQkG aef jLO YjHkG ajCJi GdYPQGg aeG CMWJ HGdeYGfi NHQG JeJ GdCQLhRI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs